Workforce as an Important Factor in Iran’s Economic Development - Mehdi, Safdari (Journal of Education and Vocational Research, 2011)
To reach higher economic growth, investment in human capital is also needed besides material investments. The purpose of this study is to determine the relationship between human capital and economic growth in Iran. The theoretical framework was designed based on this assumption that the total human capital employed in the economy is divided into two sections: Human capital with higher education and lack higher education. The data were collected from 1991 to 2006 and were analyzed using Ordinary Least Squares (OLS) model. The result of the analyses showed that there was significant relationship between human capital and economic growth. Together the independent variables explained 94% of the variance in the dependent variables. The remaining 16% was due to unidentified variables. In relation to that, we can conclude that explanatory power is high for the equation. It showed that one percent change in human capital rate lead to 58% in economic growth. Therefore human capital is regarded as an important factor in Iran’s economic growth.